Plant-Derived Food Grade Substances (PDFGS) Active Against Respiratory Viruses: A Systematic Review of Non-clinical Studies - Umeoguaju, Francis U.; Ephraim-Emmanuel, Benson C.; Patrick-Iwuanyanwu, Kingsley C.; Zelikoff, Judith T.; Orisakwe, Orish Ebere (Frontiers in Nutrition, 2021)
Human diet comprises several classes of phytochemicals some of which are potentially active against human pathogenic viruses. This study examined available evidence that identifies existing food plants or constituents of edible foods that have been reported to inhibit viral pathogenesis of the human respiratory tract. SCOPUS and PUBMED databases were searched with keywords designed to retrieve articles that investigated the effect of plant-derived food grade substances (PDFGS) on the activities of human pathogenic viruses. Eligible studies for this review were those done on viruses that infect the human respiratory tract. Forty six (46) studies met the specified inclusion criteria from the initial 5734 hits. The selected studies investigated the effects of different PDFGS on the infectivity, proliferation and cytotoxicity of different respiratory viruses including influenza A virus (IAV), influenza B virus (IBV), Respiratory syncytial virus (RSV), human parainfluenza virus (hPIV), Human coronavirus NL63 (HCoV-NL63) and rhinovirus (RV) in cell lines and mouse models. This review reveals that PDFGS inhibits different stages of the pathological pathways of respiratory viruses including cell entry, replication, viral release and viral-induced dysregulation of cellular homeostasis and functions. These alterations eventually lead to the reduction of virus titer, viral-induced cellular damages and improved survival of host cells. Major food constituents active against respiratory viruses include flavonoids, phenolic acids, tannins, lectins, vitamin D, curcumin and plant glycosides such as glycyrrhizin, acteoside, geniposide and iridoid glycosides. Herbal teas such as guava tea, green and black tea, adlay tea, cistanche tea, kuding tea, licorice extracts and edible bird nest extracts were also effective against respiratory viruses in vitro. The authors of this review recommend that the consumption of foods rich in these PDFGS including legumes, fruits (e.g berries, citrus), tea, fatty fish and curcumin be consumed in elevated amount amongst human populations with high prevalence of respiratory viral infections in order to prevent, manage and/or reduce the severity of respiratory virus infections.